A comparison of the lateral tarsal strip with everting sutures and the Quickert procedure for involutional entropion. Issue 6 (27th March 2019) - Dulz, Simon; Green, Sylvia; Mehlan, Juliane; Schüttauf, Frank; Keserü, Matthias
Abstract: Background/Aims: To provide evidence of statistically significant difference in the surgical outcome of the lateral tarsal strip with everting sutures (LTS + ES) versus the Quickert procedure (QP) in the treatment of involutional entropion. Methods: In a prospective randomized comparative trial, 66 eyelids of 52 patients with primary involutional lower eyelid entropion were recruited. Thirty‐six eyelids were randomized to QP, and 30 eyelids were randomized to LTS + ES. Surgery was performed by a single surgeon. Postoperative follow‐up was scheduled after 2 weeks, 8 and 14 months. Successful surgery was defined as a normal eyelid position at rest and inability to induce entropion on forced eyelid closure at or before the 14‐month follow‐up visit. Results: A total of 66 eyelids of 52 patients were enrolled in the study. Three patients did not complete follow‐up (1 did not attend the 8 months follow‐up visit; 2 did not attend 14 months follow‐up visit). Of the 63 patients, a single eyelid [success probability 0.97; confidence interval (CI) 0.92–1] in the QP group and two treated eyelids [success probability of 0.93; CI: 0.85–1] in the LTS + ES group had a recurrence of a lower eyelid entropion after 14 months. There was no statistically significant difference in surgical failure between the LTS + ES versus QP (Log‐rank test: p = 0.46). Conclusion: These data provide strong evidence that success rates at 14 months are similar in patients treated with either techniques (LTS + ES versus QP).